TWO NEW SPECIES AND A NEW RECORD OF GENUS PERIACMA MEYRICK FROM NORTH INDIAN STATES (LEPIDOPTERA : OECOPHORIDAE : OECOPHORINAE) - WALIA, V.K.; WADHAWAN, D. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2011)
Intensive and extensive surveys of different localities in the two North Indian states, namely Himachal Pradesh and Haryana (including Chandigarh) conducted between 20002004 brought to light three species of genus Periacma Meyrick belonging to subfamily Oecophorinae of family Oecophoridae. These include two new species i.e. un equispinosa and trispinosa and an already described species plumbea Meyrick, reported from Kumaon and Bhimtal in Uttaranchal. Present communication includes illustrations of wing venation and genitalia of both the sexes of the three investigated species. In addition, detailed descriptions of both the new and salient features of the already recorded species are given.